Curriculum Management of Sufism-Based Character Education in Early Childhood: A Case Study of the Tasawuf for Kids Program at RA Idrisiyyah Pagendingan - Devitri Awalliyah; Rizal Fauzi; Syafrudin Syafrudin (STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to analyze the management of Sufism-based character education curriculum implemented through the Tasawuf for Kids program at Raudhatul Athfal (RA) Idrisiyyah Pagendingan. Employing a qualitative case study design, the research involved seven purposively selected participants, including the school principal, curriculum coordinator, and classroom teachers. Data were collected through participant observation, in-depth interviews, and document analysis and were analyzed using the interactive model of Miles and Huberman, supported by coding procedures. The findings reveal that curriculum planning has not yet been formally documented but is implicitly embedded within the institution’s vision and educational philosophy. Curriculum implementation is realized through the habituation of adab (Islamic etiquette), religious practices, and teacher role modeling within the tarekat-based institutional culture. Curriculum evaluation is conducted primarily through classroom observation without the support of standardized assessment instruments. Supporting factors include teachers’ strong commitment and the institution’s conducive spiritual environment, whereas inhibiting factors consist of the absence of formal curriculum documentation and standardized evaluation instruments. Overall, the findings indicate that the management of the Sufism-based curriculum demonstrates an adaptive approach that effectively supports character education in early childhood. The study contributes to the discourse on curriculum management by highlighting the integration of Sufistic values into early childhood education and provides practical implications for strengthening spirituality-based character education within Islamic educational institutions.